Time management and procrastination during the COVID-19 pandemic in higher education - Rini Sefriani; Krisnova Nastasia; Rina Sepriana; Yeki Candra (Intelektual Pustaka Media Utama, 2022)
Online learning is enforced by all higher education in Indonesia due to the COVID-19 pandemic. There is an inability of students to manage time and often delay the work given by the lecturer. This study aimed to reveal the degree of relationship between student time management and academic procrastination in higher education. This research was conducted at the Psychology Faculty of the University Puta Indonesia YPTK Padang, Indonesia. The sample of this research was psychology students as many as 202 respondents. The research instrument was in the form of a questionnaire distributed via Google Form. The results showed that the level of correlation between time management and academic procrastination of psychology students was 0.242 with data processing using SPSS 26. Which means that there is a relationship between students' ability to manage time and delay in completing assignments by students of the faculty of psychology. The role of lecturers in providing direction and motivation to students is very much needed.